A control strategy on power quality improvement in consumer side using custom power device - D Danalakshmi; Srinivas Bugata; Kohila J (Institute of Advanced Engineering and Science, 2019)
At a recent time voltage distortion is one of the foremost power quality problem at all level of power system. Power electronic controllers like various filtering technology have been used for more desirable solution of power quality problems to users. But still there is a voltage and frequency deviations problem in the power system leads to reduce in quality of power and thereby reduce the life of consumer equipment. To overcome this drawback and protects the sensitive loads from power quality problems, custom power devices are used. Among various custom power devices, Dynamic voltage restorer (DVR) is an ultimate solution to address the voltage correlated power quality problems. DVR is a usual three phase inverter which transforms DC to AC and vice-versa using DC link capacitor. Whenever utility is distorted by voltage correlated faults, DVR is dynamic and it shields the load from utility distortions. Whenever distortion arises, the control strategy for the DVR plays significant role to make the DVR in active condition. Among all control strategies, Synchronous reference frame theory is simple and suitable for DVR. The DVR topology is verified and validated using SIMULINK/MATLAB.